Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.22237/jmasm/1478002380
|View full text |Cite
|
Sign up to set email alerts
|

A New Exponential Type Estimator for the Population Mean in Simple Random Sampling

Abstract: This paper provides a new exponential type estimator in simple random sampling for population mean. It is shown that proposed exponential type estimator is always more efficient than estimators considered by Bahl and Tuteja (1991) and Singh, Chauhan, Sawan, and Smarandache (2009). From numerical examples it is also observed that proposed modified ratio estimator performs better than existing estimators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Table 2 represents the control chart multipliers 𝐾 , defined in Equation (15) for correlations 𝜌 = 0.20, 0.50, 0.80 and 0.95 and 𝑛 = 10. Mathematics 2020, 8, x FOR PEER REVIEW 10 of 21 defined in Equation (18). Table 2 represents the control chart multipliers 𝐾 , defined in Equation (15) for correlations 𝜌 = 0.20, 0.50, 0.80 and 0.95 and 𝑛 = 10.…”
Section: Performance Evaluation Of Median Control Charts In Phase Imentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 represents the control chart multipliers 𝐾 , defined in Equation (15) for correlations 𝜌 = 0.20, 0.50, 0.80 and 0.95 and 𝑛 = 10. Mathematics 2020, 8, x FOR PEER REVIEW 10 of 21 defined in Equation (18). Table 2 represents the control chart multipliers 𝐾 , defined in Equation (15) for correlations 𝜌 = 0.20, 0.50, 0.80 and 0.95 and 𝑛 = 10.…”
Section: Performance Evaluation Of Median Control Charts In Phase Imentioning
confidence: 99%
“…The auxiliary information, i, enhances the precision of estimator(s) or improves the sampling plan. There are several studies in literature of survey sampling available for the use of auxiliary information and it has been conclusively shown that the use of auxiliary information enhances the accuracy of estimators for population mean [18], population median [19] or population variance [20].…”
Section: Introductionmentioning
confidence: 99%
“…Estimators Srivastava (1967), Reddy (1974), Nangsue (2009), Kadilar (2016), Soponviwatkul and Lawson (2017), Ijaz and Ali (2018 Bahl and Tuteja (1991 Kadilar and Cingi (2003 Sisodia and Dwivedi (1981), Upadhyaya and Singh (1999), Singh and Tailor (2003), Singh et al (2004), Al-Omari et al (2009, Yan and Tian (2010), Kumarpandiyan (2012a, 2012b), Jeelani et al (2013), Jerajuddin and Kishun (2016) estimators International Journal of Mathematical, Engineering and Management Sciences Vol. 4, No.…”
Section: Efficiency Conditionmentioning
confidence: 99%
“…Grover and Kaur [8] suggested a generalized class of exponential-ratio-type exponential estimators using the conventional measures for mean estimation. Kadilar [9] discussed a new exponential-type estimator for mean estimation. Irfan et al [10] suggested a generalized ratio-exponential-type estimator using the conventional measures.…”
Section: Introductionmentioning
confidence: 99%